Strategi Pemenangan Bonaran Situmeang dan Syukran Tanjung dalam Pemilukada Tapanuli Tengah Tahun 2011 - Agustina Manalu (Dinamika Politik, 2012)
This study is the study winning of strategy Bonaran Situmeang and Syukran Tanjung in Central Tapanuli in election year 2011. The focus is about how winning strategy Bonaran Situmeang and Syukran Tanjung in Central Tapanuli local elections in 2011. The findings of this study, among others, there are two important things in strategy and Syukran Tanjung Bonaran include successfully take into account the importance of building relationships and emotional harmony to the society as a capital to gain sympathy and support from the voting public. Both Bonaran and Syukran Tanjung successfully formulate their programs realistic, relevant to all the problems in the Middle Tapanuli district. The method used is a qualitative method diskriprif an event that is intended to describe in detail.